Delayed onset isolated post-traumatic sixth nerve palsy due to trendelenburg position: an unusual cause - Thapa, Anil; Shrestha, Dibesh; Giri, Sandarva (Journal of Kathmandu Medical College, 2014)
We report here an unusual case of post-traumatic isolated sixth nerve palsy occurring while nursing the patient in trendelenburg position. This is the first case to be reported in the available literature of posture induced delayed onset isolated post-traumatic sixth nerve palsy and highlights importance of avoiding head down position while nursing patients with head injury. DOI: http://dx.doi.org/10.3126/jkmc.v3i1.10921 Journal of Kathmandu Medical College Vol. 3, No. 1, Issue 7, Jan.-Mar., 2014, Page: 32-33